Associations of Reproductive Health Knowledge and Attitudes with Menstrual Hygiene Behaviors among Adolescent Girls at Al Muflihun Islamic Boarding School, Malang - Hazna Dinda Tyafarda; Ratih Paramita Suprapto; Ningrum Paramita Sari; Lilik Indahwati (Journal Of Nursing Practice, 2026)
Background: Adolescents' emotional responses to menarche tend to vary, including anxiety, confusion, and embarrassment, often linked to their knowledge. Lack of knowledge about reproductive health can influence adolescents’ attitudes and behaviors during menstruation. For example, inadequate menstrual hygiene practices may lead to various health issues. Purpose: This study aimed to examine whether reproductive health knowledge predicts adolescents' attitudes and menstrual hygiene behaviors, and whether attitudes predict menstrual hygiene behaviors among female students at Al Muflihun Islamic Boarding School in Malang. Methods: This study used a cross-sectional design with an analytic observational approach. A total of 48 female students aged 10–17 years were selected through total sampling. Data were collected using structured questionnaires and analyzed using regression-based path analysis. Results: Results showed that 68.8% of respondents had good knowledge, 25.0% had moderate knowledge, and 6.3% had poor knowledge. Additionally, all respondents (100%) demonstrated positive attitudes and good behaviors in dealing with menstruation. Regression-based path analysis using continuous questionnaire scores showed that reproductive health knowledge significantly predicted attitude (β=0.675; p=0.000) and behavior (β=0.334; p=0.032), while attitude also predicted behavior (β=0.392; p=0.013). Conclusion: These findings support Lawrence Green’s theory, which states that predisposing factors such as knowledge and attitude affect health behavior. Therefore, more intensive and continuous reproductive health education in schools can improve awareness and menstrual hygiene practices among adolescent girls.